A high-quality genome assembly and annotation of Quercus acutissima Carruth - Liu, Dan; Xie, Xiaoman; Tong, Boqiang; Zhou, Chengcheng; Qu, Kai; Guo, Haili; Zhao, Zhiheng; El-Kassaby, Yousry A.; Li, Wei; Li, Wenqing (Frontiers in Plant Science, 2022)
Quercus acutissima is an economic and ecological tree species often used for afforestation of arid and semi-arid lands and is considered as an excellent tree for soil and water conservation. Here, we combined PacBio long reads, Hi-C, and Illumina short reads to assemble Q. acutissima genome. We generated a 957.1 Mb genome with a contig N50 of 1.2 Mb and scaffold N50 of 77.0 Mb. The repetitive sequences constituted 55.63% of the genome, among which long terminal repeats were the majority and accounted for 23.07% of the genome. Ab initio, homology-based and RNA sequence-based gene prediction identified 29,889 protein-coding genes, of which 82.6% could be functionally annotated. Phylogenetic analysis showed that Q. acutissima and Q. variabilis were differentiated around 3.6 million years ago, and showed no evidence of species-specific whole genome duplication. The assembled and annotated high-quality Q. acutissima genome not only promises to accelerate the species molecular biology studies and breeding, but also promotes genome level evolutionary studies.